The Effect of Chance Variation on Revenue and Cost Estimations for Breakeven Analysis: A Comment. - Chen, Joyce T. (The Accounting Review, 1983)
The article presents a comment on the effect of chance variation on revenue and cost estimations for breakeven analysis. In traditional breakeven analysis, total revenue and total cost are represented by straight lines with one intersection which indicates the breakeven quantity output. The effect of quadratic revenue and cost curves on breakeven analysis was introduced. Two breakeven points for the quadratic model were derived by solving for the levels of output at which the regressed total revenue equals total cost. Regardless of whether a linear or non-linear breakeven model may be appropriate, however, the revenue and cost functions are often unknown. Givens illustrated the regression analysis, but did not consider the effect of regression forecasting errors. In order to resolve the above issue an attempt was made to demonstrate the determination of what he called "the chance variation" in estimated revenue and cost functions; and to illustrate how these chance variations affect the results of a breakeven analysis. The estimated cost-volume functions were subtracted from the estimated revenue-volume functions to derive an estimated profit-volume function.